The Nexus of Financial Stability and Bank Specific Risks: Evidence from the Nepalese Banking Sector - Dhakal, Bhimlal (Devkota Journal of Interdisciplinary Studies, 2024)
This study examines the correlation between the financial stability of Nepali commercial banks and bank-specific risks by utilizing panel data from 20 commercial banks over a 12-year period from 2011 to 2023. The findings, which were obtained through the use of a fixed-effect model, demonstrate that bank-specific risks – notably liquidity risk and credit risk – present a significant threat to the stability of banks. Conversely, there is no discernible impact of funding risk on financial stability. Furthermore, larger banks have a detrimental effect on stability, while return on assets (ROA) has a beneficial effect on financial resilience. In order to preserve long-term stability, bank management must establish prudent policies that guarantee the safe disbursement of loans and the prompt repayment of the same, thereby mitigating credit risk. Additionally, it is imperative to maintain a proactive approach to liquidity management and effectively mobilize client deposits in order to achieve robust financial stability.